2023
DOI: 10.1093/bjs/znad042
|View full text |Cite
|
Sign up to set email alerts
|

Surgical interhospital transfer mortality: national analysis

Abstract: Background Interhospital transfers of surgical patients are an independent risk factor for mortality. The Australian and New Zealand Audit of Surgical Mortality (ANZASM) aims to improve surgical care through assessment of all cases of surgical mortality. This study aimed to describe common clinical management issues that contributed to interhospital transfer patient mortality. Methods Data for all surgical patient mortality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…There were four clinical incidents where assessors noted inadequate fluid resuscitation, with responsibility attributed to the transferring hospital, 17,18 emergency department (ED) and in two cases the surgical team. In four cases, it was felt by assessors that the patient would have benefited from admission to the ICU, due to medical complexity and severity of disease.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were four clinical incidents where assessors noted inadequate fluid resuscitation, with responsibility attributed to the transferring hospital, 17,18 emergency department (ED) and in two cases the surgical team. In four cases, it was felt by assessors that the patient would have benefited from admission to the ICU, due to medical complexity and severity of disease.…”
Section: Resultsmentioning
confidence: 99%
“…In the second case the assessor commented that the patient would have benefited from a general anaesthetic (GA) rather than sedation, as it may have helped the patient tolerate the difficult therapeutic intervention, and potentially prevent the ensuing desaturation and collapse. It has been found that a GA is associated with reduced complications of therapeutic ERCP intervention when compared with conscious sedation, attributed to reduced movement and duodenal aperistalsis 17 . Thus in a patient with five large stones and one impacted in the proximal common bile duct, GA may have prevented the need for repeat ERCP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, overnight referrals were also more likely to be assigned to the red pathway. Overnight referrals are variably described in the literature, but frequently attributed to referring hospital resource limitations 25,26 . For burn injuries requiring time- and resource-intensive care, referring providers may feel constrained when staffing is limited overnight.…”
Section: Discussionmentioning
confidence: 99%